# algebra

1. 👍 0
2. 👎 0
3. 👁 92
1. I will assume the usual carelessness with parentheses, and that you mean

(7y+5)/3 = -8/(y-3)

Clear fractions (assuming y≠3) and we have

(7y+5)(y-3) = -8(3)
7y^2 - 16y - 15 = -24
7y^2 - 16y + 9 = 0
(7y-9)(y-1) = 0
y = 1 or 9/7

1. 👍 0
2. 👎 0
posted by Steve

## Similar Questions

1. ### math

what is the procedure for solving the equation 1/2x = 16. I am stuck. Please help me.

asked by Jay on April 9, 2015
2. ### Pre-Calc

I am stuck solving this problem, any help please..Many thanks find all numbers x that satisfy the given equation ln(2x) ------- =2 ln(3x)

asked by Roy on December 9, 2010
3. ### math

hi! so I have almost finshed solving a math equation i'm just stuck on this one last thing: x^3=3.85x10^-17 and I don't know how to isolate for x! plz help

asked by isabella on January 11, 2016
4. ### Pre-Calculus

I need help solving this logarithmic equation: ln x + ln (x+3) = 1. I know ln x + ln (x+3)=ln [x(x+3)] and that is ln x^2 + 3x when broken down. Then you have to get rid of ln by taking the natural base e of both sides so in the

asked by Kelsey on May 3, 2008
5. ### math

Hi I need help with this math problem: The plane that contains the points (8,3,1), (2,6,3), and (4,6,2) has an equation of the form ax + by + cz = d. Find coefficients for this equation, trying two different approaches to the

asked by jen on July 29, 2010
1. ### Calculus

Hello, I would greatly appreciate any help that I can have with the following calculus question below. It has to do with separable differential equations. I'm also going to explain what I've done so far, so please bear with me

asked by Stephen on April 16, 2017
2. ### math

Let F1 = (0,2), F2 = (0,-2), and P = (x,y). Use the distance formula to convert the equation PF1 + PF2 = 6 into Cartesian form. Simplify your answer until it reaches the form hx^2+ky^2=m. I tried solving this but I got stuck with

asked by maath on August 9, 2018
3. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

asked by SANDRO! on November 6, 2006
4. ### Math

9(x+2)(x+1)-2(x+2)-4(x+1)=0 I'm in the middle of solving an equation. I know that you have to FOIL but how did they get 9(x^2+3x+2)-(4x+4)=0 ? I thought you distribute the 9 through (x+2)(x+1). and why is it (4x+4) instead of

asked by Beth on June 9, 2013
5. ### physics

Stuck on solving for unknowns in part F and G help please? a) the upper loop 1 18I12+ 13I18=30 (b) the lower loop 2 =5.00I36 - 18I12= 24 (c) the node on the left side 3 I12+I36=I18 (d) Solve the node equation for I36. 4 I12 - I18

asked by MIKE on February 23, 2015

More Similar Questions